(Des)cobrir-me: minhas impressões afro-brasileiras - Rosa, Thais Oliveira da (2022)
The study deals with Afro-Brazilian culture, presented through photographs from the 19th century. In this sense, this research builds an approximation to this culture through the visuality and artistic processes that are inserted in the poetics, in front of Afrodiasporic authors and decolonial studies. Concepts such as self-assessment and selfdetermination were also used, as well as devices and profanation that dialogue in the creation of subjectivities. Aiming to understand how I (Dis)discover myself through the molds that poetics evokes in me, this study was developed from experiments in selfportraits and expanded techniques with woodcuts, weaving connections between personal and artistic processes through the search for ( Un)covering and reframing the look on oneself from the look on the other. With this, the research allows the confrontation between past and present through the juxtaposition of visualities of photographs of the 19th century and discusses the origins of Afro-Brazilian narratives that tell the history of the black population from another perspective. It was observed, therefore, the power and place of the color black in the construction of the artistic process and in my direction as a person, artist, but - mainly - as an Afro-Brazilian person. It is concluded, therefore, that the development of the concept of (Un)covering oneself deepened the cultural and aesthetic aspects of the color black along with the act of covering self-portraits with black paint, a characteristic that presents itself as an inheritance of my artistic process that began in contact with engraving techniques. The color black has always been an important part of the visual construction of my artistic works, precisely because they portray black people and explore the visuality and expression of color on black skin. The development of this concept materialized, together with the works presented, the research objectives of establishing the confrontation between past and present and the (Dis)covering of oneself through the relationship between personal and artistic processes.